Aplikasi Android Kamus Bahasa Indonesia-Sasak - Lalu Erwin Haris; Ahmad Susan Pardiansyah (Jurnal Manajemen Informatika dan Sistem Informasi, 2018)
Sasak language is one of the local languages ​​used to communicate by people of Lombok, West Nusa Tenggara. But along with the development of technology, especially in the field of smartphones, Sasak language has begun to fade, not the least of Lombok people who do not understand the language vocabulary Lombok Sasak especially the current generation. It is caused by environmental factors family, school and friends that use the Indonesian language in everyday conversation. The solution to these problems is to design an application Indonesian-Sasak dictionary based on Android. The main purpose of a dictionary application Indonesian-Sasak is to help them in finding a translation in Indonesian or Sasak language effectively and efficiently with the media smartphone. There are several stages in the making of this application, which analyzes the data by the method of SWOT analysis, application design using SDLC, the process of working with UML, and the implementation of the program model that has been generated. Indonesian-Sasak dictionary application android generated based APPS shaped installer that can be used on Android-based smartphones with minimal version 2.2 Up to 5.0. In testing using the Black-box testing and trials on smartphones, applications can run smoothly.